Anomalous Evidence, Confidence Change, and Theory Change. (1st October 2015) - Hemmerich, Joshua A.; Van Voorhis, Kellie; Wiley, Jennifer
Abstract: A novel experimental paradigm that measured theory change and confidence in participants' theories was used in three experiments to test the effects of anomalous evidence. Experiment 1 varied the amount of anomalous evidence to see if "dose size" made incremental changes in confidence toward theory change. Experiment 2 varied whether anomalous evidence was convergent (of multiple types) or replicating (similar finding repeated). Experiment 3 varied whether participants were provided with an alternative theory that explained the anomalous evidence. All experiments showed that participants' confidence changes were commensurate with the amount of anomalous evidence presented, and that larger decreases in confidence predicted theory changes. Convergent evidence and the presentation of an alternative theory led to larger confidence change. Convergent evidence also caused more theory changes. Even when people do not change theories, factors pertinent to the evidence and alternative theories decrease their confidence in their current theory and move them incrementally closer to theory change.